The Effect Of Plant Spacing And Number Of Plants Per Planting Hole On The Growth And Production Of Okra (Abelmoschus esculentus L. Moench) - Al Machfudz WDP; Widya Ningsih (Nabatia, 2017)
The study was aimed at determining the effect of plant spacing and number of plants per planting hole on the growth and production of okra. This research was conducted in paddy fields Rodowo Village, Beji District, Pasuruan which took place starting at Febru- ary 2016 until May 2016. Factorial research using a Randomized Block Design (RBD) is repeated three times. The first factor is the spacing of treatment includes three levels is 25 cm x 75 cm (J1), 35 cm x 75 cm (J2) and 45 cm x 75 cm (J3), while the second factor is the treatment the number of plants per planting hole that is 1 plant (T1), 2 plants (T2) and 3 plants (T3). The acquired data was analyzed by analysis of variety and in further tests using HSD level of 5%. Based on observations made that the interaction between plant spacing and number of plants per planting hole on the growth and production of okra, but the production of okra per unit area (ha) in the treatment plant spacing gives the best effect, namely a spacing of 25 cm x 75 cm with a weight production reached 19,64 tons/ha, whereas the treatment the number of plants per planting hole gives the best effect is in the amount of 3 plants per planting hole with heavy production reached 5,36 tons/ha.